2019
DOI: 10.1590/s1517-707620190001.0605
|View full text |Cite
|
Sign up to set email alerts
|

Study of the structural and morphological properties of copper catalysts supported on Al2O3 and TiO2 synthesized by the impregnation method

Abstract: Aluminum oxide and titanium oxide are widely used as catalytic support. Due to their characteristics and properties, they have several applications such as chemical processes, photocatalysis and pollution control. In this work, the catalytic supports of Al 2 O 3 and TiO 2 were impregnated with 2% of copper oxide by the method of impregnation. The catalysts were characterized by X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Brunauer-Emmett-Telle (BET) surface area and Infrared Spectroscopy techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
(35 reference statements)
1
2
0
Order By: Relevance
“…This is an expected pattern and can be attributed to the pore filling by the added Cu 2+ and Pd 2+ which are incorporated and entrapped in the cavities of the support [ 9 , 12 ]. Similar decrease of BET surface area upon metal doping was reported by De Queiroz et al and Wang et al in their study of Cu/TiO 2 –Cu/Al 2 O 3 catalysts and Pd/Cu/MOx (MOx=TiO 2 and Al 2 O 3 ) catalysts, respectively [ 9 , 40 ]. Hossain et al also shows that both pore volume and surface area decreased upon incorporation of Cu in the titanium nanotube structure [ 29 ].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This is an expected pattern and can be attributed to the pore filling by the added Cu 2+ and Pd 2+ which are incorporated and entrapped in the cavities of the support [ 9 , 12 ]. Similar decrease of BET surface area upon metal doping was reported by De Queiroz et al and Wang et al in their study of Cu/TiO 2 –Cu/Al 2 O 3 catalysts and Pd/Cu/MOx (MOx=TiO 2 and Al 2 O 3 ) catalysts, respectively [ 9 , 40 ]. Hossain et al also shows that both pore volume and surface area decreased upon incorporation of Cu in the titanium nanotube structure [ 29 ].…”
Section: Resultssupporting
confidence: 80%
“…The N 2 adsorption/desorption isotherms for selected mono- and bi-metallic catalysts, namely Cu-TNW and Pd-Cu-TNW are presented in Figure 3 . Both catalysts show type IV isotherms and H3 hysteresis loop indicating mesoporous structure with pore width in the range of 2–50 nm according to IUPAC classification [ 33 , 40 ]. The hysteresis loop appearing in the multilayer range of physisorption isotherms is attributed to capillary condensation taking place in the mesopores [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The method depends on the metal cation, which becomes a dopant. Queiroz and Barbosa [17] reported that the synthesis of Cu-TiO2 by the impregnation method could be obtained by anatase phase TiO2. Behnajady and Eskandarloo [18] reported the same thing.…”
Section: Introductionmentioning
confidence: 99%